(untitled) (Communications in Mathematical Research, 2019)
In this paper, a class of mixed monotone operators is studied. Some new fixed point theorems are presented by means of partial order theory, and the uniqueness and existence of fixed points are obtained without assuming the operator to be compact or continuous. Our conclusions extend the relevant results. Moreover, as an application of our result, the existence and uniqueness of positive solution for a class of fractional differential equation boundary value problem are proved.